2013
DOI: 10.1371/journal.pone.0057023
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression Pattern of Molecular Factors Involved in Colonic Smooth Muscle Functions: An Immunohistochemical Study in Patients with Diverticular Disease

Abstract: BackgroundThe pathogenesis of diverticular disease (DD) is thought to result from complex interactions among dietary habits, genetic factors and coexistence of other bowel abnormalities. These conditions lead to alterations in colonic pressure and motility, facilitating the formation of diverticula. Although electrophysiological studies on smooth muscle cells (SMCs) have investigated colonic motor dysfunctions, scarce attention has been paid to their molecular abnormalities, and data on SMCs in DD are lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Immunohistochemical studies indicate that Cx26, Cx32 and Cx43 are expressed at the protein level in the normal colon in humans . The connexins localize in intracellular compartments, but also in distinct, punctuate plasma membrane domains likely representing gap junctions.…”
Section: Expression Of Connexins In the Normal Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical studies indicate that Cx26, Cx32 and Cx43 are expressed at the protein level in the normal colon in humans . The connexins localize in intracellular compartments, but also in distinct, punctuate plasma membrane domains likely representing gap junctions.…”
Section: Expression Of Connexins In the Normal Colonmentioning
confidence: 99%
“…Immunohistochemical studies indicate that Cx26, Cx32 and Cx43 are expressed at the protein level in the normal colon in humans. [77][78][79][80][81][82][83] The connexins localize in intracellular compartments, but also in distinct, punctuate plasma membrane domains likely representing gap junctions. The notion that connexins are able to form gap junctions in normal colonic mucosa is further supported by Western blot analysis of protein extracts from normal colon tissue.…”
Section: Expression Of Connexins In the Normal Colonmentioning
confidence: 99%
“…Thus, symptoms related to abnormal (hypercontractile) patterns of colonic motor functions in DD patients might depend, at least in part, upon the alterations highlighted in our study. Of course, other abnormalities, such as those related to colonic smooth muscle (Mattii et al, 2013) and mast cells within the colonic layers (Bassotti et al, 2013), are likely also to play pathophysiological roles, and it is possible that the summation of different abnormalities leads to the generation of dysmotilityrelated (Bassotti and Villanacci, 2012) and sensory (Clemens et al, 2004) abdominal symptoms often reported by patients with DD.…”
Section: Figurementioning
confidence: 99%
“…Notably, DD has been associated also with neuromuscular dysfunctions (Bassotti et al, 2001;Bassotti and Villanacci, 2012). Colonic motor abnormalities in DD have been hypothesized to result from changes in enteric nerves, smooth muscle functions (Golder et al, 2003;Bassotti et al, 2005a;Mattii et al, 2013), and low-grade mucosal and myenteric inflammation (Bassotti et al, 2013). In addition, alterations in the excitatory control by enteric cholinergic nerves have been observed in DD, but not by all groups (Tomita et al, 2000;Golder et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cx26 has been described in a number of tissues but not in the heart and its mutations are frequently associated with deafness and skin diseases 6 , 7 . An altered expression of Cx26 in colonic smooth muscle cells may predispose the formation of diverticular lesions 8 while the reduced expression of Cx26 may contribute to the low sensitivity of hepatocellular carcinoma towards the chemotherapeutic agent oxaliplatin 9 .…”
Section: Introductionmentioning
confidence: 99%